Interpretative conflicts, regulatory gaps and pending tasks to strengthen the legal regime for environmental impact assessment - García Cerrón, Erick Leddy (2022)
This article takes a critical look at the application of the National Environmental Impact Assessment System. Thus, recognizing the importance of this legal regime to empower the role of the State in the environmental management of investment projects, as well as the prevention of socio-environmental conflicts, a review of the current institutional framework is carried out, specifically the changes and advances regarding the exercise of functions by Senace. In this line, the scope of an interpretative conflict related to the scope of non-significant environmental impacts on bodies of water is presented. Likewise, a critical view of the corrective environmental management instruments is presented. Finally, some ideas are presented regarding the procedure for updating environmental studies as a mechanism for the continuous improvement of environmental management instruments.